2017
DOI: 10.1007/s00240-017-0989-7
|View full text |Cite|
|
Sign up to set email alerts
|

Different effects of γ-linolenic acid (GLA) supplementation on plasma and red blood cell phospholipid fatty acid composition and calcium oxalate kidney stone risk factors in healthy subjects from two race groups with different risk profiles pose questions about the GLA-arachidonic acid-oxaluria metabolic pathway: pilot study

Abstract: Fatty acid (FA) composition of phospholipids in plasma and red blood cells (RBC) can influence calciuria, oxaluria and renal stone formation. In this regard, the ratio of arachidonic acid (AA) and its precursor linoleic acid (LA) appears to be important. Administration of γ-linolenic acid (GLA) has been shown to increase the concentration of dihomo-gamma linoleic acid (DGLA) relative to AA indicating that it may attenuate biosynthesis of the latter. Such effects have not been investigated in race groups having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…They suggested that this inconsistency might be due to differences in their respective patient cohorts as their earlier study involved hypercalciuric patients while their subsequent study did not [5]. Interestingly, Table 1 shows that four of the other studies in which no decrease in urinary Ca occurred used healthy subjects as their test group as opposed to stone-formers [6,10,14,25] lending support to the notion that PUFA-induced reduction of Ca excretion is possibly restricted to stone-forming patients. Indeed, Buck and co-workers commented in an earlier paper that the normalizing effect of fish oil with respect to urinary calcium and oxalate levels was more pronounced in patients in whom these parameters were markedly raised [1].…”
Section: Pufa Dietary Interventionsmentioning
confidence: 96%
See 4 more Smart Citations
“…They suggested that this inconsistency might be due to differences in their respective patient cohorts as their earlier study involved hypercalciuric patients while their subsequent study did not [5]. Interestingly, Table 1 shows that four of the other studies in which no decrease in urinary Ca occurred used healthy subjects as their test group as opposed to stone-formers [6,10,14,25] lending support to the notion that PUFA-induced reduction of Ca excretion is possibly restricted to stone-forming patients. Indeed, Buck and co-workers commented in an earlier paper that the normalizing effect of fish oil with respect to urinary calcium and oxalate levels was more pronounced in patients in whom these parameters were markedly raised [1].…”
Section: Pufa Dietary Interventionsmentioning
confidence: 96%
“…Finally, Rodgers et al argued that the significantly lower occurrence of stones in South Africa's black population relative to that in the white population presented them with an ideal opportunity to test whether PUFAs might play a role in this anomaly. They examined PUFA plasma and urinary profiles in their low-and high-risk groups B and W, respectively [15,25], and reported findings that were also counterintuitive relative to the Baggio model [11]. The concentration of AA was significantly higher in the low-risk B group, and there was no difference between the groups in AA/LA ratios [15].…”
Section: Low-risk Groupsmentioning
confidence: 99%
See 3 more Smart Citations